Formation of meaning in the relationship between the audience and the theatrical discourse in the contemporary Iraqi theatre (Journal of the College of Basic Education, 2022)
The research summarizes the process of forming meaning through the relationship between the recipient and the theatrical discourse. The process of forming meaning in theatrical discourse is characterized as a comprehensive process that the recipient receives and tries to understand its meanings through the unity of its parts and their fusion with the theatrical process as a whole. The process of forming meaning is a relative aesthetic process that is determined by the type of that relationship and the nature of its formation.Theatrical discourse is a human message addressed to a specific audience. Some theatrical discourses are characterized by the wideness of their aesthetic spaces, as they are directed to humanity as a whole, so that the recipient anywhere in the world can form their meanings, fill their white gaps, and form a horizon of expectations through the positive relationship between him and the discourse. A large segment of people, and the best example of this is Shakespeare's theater, which was translated from his original language into all languages of the world and received positive interaction by the general public and was subject to many contextual and systemic studies alike by theater specialists all over the world and to this day it is covered by many studies Arabic and many others like Ibsen's theater and the immortal experiences of Brecht. However, some Western and Arabic discourses in general and Iraqi discourses in particular were distinguished by being local discourses addressed to a specific recipient who alone can decipher its symbols, interpret its riddles and form the meaning of the discourse according to its contextual relationship to it. This research came to study that relationship through Three chapters The first chapter is the methodological framework for the research. Spatial research Presentations of the professors of the Faculty of Fine Arts and temporal boundaries from the year (2010) to the year (2016) and the second chapter, the theoretical framework, which consists of three topics, the first topic: the concept of meaning, and the second topic: is the relationship of meaning to the recipient and the third topic: the aesthetics of meaning in theatrical discourse The research dealt with previous studies, which consisted of two studies, the first was by the researcher Omar Farouk Muhammad, who submitted it to the Council of the College of Fine Arts in 2014 AD, which is a master's thesis entitled ((The function of reading and receiving in the formation of meaning)) and the second study was by the researcher Muntadhar Khudair Mohsen, a master's thesis, Submitted to the Council of the College of Fine Arts in 2016 (not discussed yet)Entitled ((Dialectical Meaning and Expectation Consistent in the Experiences of Contemporary Iraqi Theatre)), the research showed the most important indicators that came from the Al-Nadhari framework, and the third chapter included research procedures and dealt with the play ((Adam's Ship)) as a sample for analysis.The work is wonderful, from the masterpieces of a group of academic artists, written by the creative Ali Abdel Nabi Al-Zaidi, directed by Dr. Yassin Ismail Al-Kaabi, and represented by the able actress, Dr. Shatha Salem, Dr. Khaled Ahmed Mustafa, the actor Basman Mokhles, and the actor Sarmad Ahmed, the music of Dr. Saleh Mahdi Al-Fahdawi, and the scenography of Durgham Al-Bayati. The show was on the stage of an art workshop Theater at the College of Fine Arts. The fourth chapter is the results and conclusions and the most important sources on which the research and the conclusion were based.